2014
DOI: 10.1128/mcb.01633-13
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Is Required for Kinase Suppressor of Ras 1 (KSR1)-Mediated Extracellular Signal-Regulated Kinase 1/2 Activation, H-RasV12-Induced Senescence, and Transformation

Abstract: The molecular scaffold kinase suppressor of Ras 1 (KSR1) regulates the activation of the Raf/MEK/extracellular signal-regulated kinase (ERK) signal transduction pathway. KSR1 disruption in mouse embryo fibroblasts (MEFs) abrogates growth factor-induced ERK activation, H-Ras V12 -induced replicative senescence, and H-Ras V12 -induced transformation. Caveolin-1 has been primarily described as a major component of the coating structure of caveolae, which can serve as a lipid binding adaptor protein and coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…KSR1 is an essential scaffold protein of the Ras/Raf/MAPK cascade that facilitates the activation of ERK (3). Studies have shown that the expression of KSR1 is upregulated in many types of cancer and is required for cell proliferation, apoptosis and cell-cycle reinitiation (4)(5)(6). Moreover, KSR1 was confirmed to contribute to tumorigenesis through the MAPK cascade in a mouse model (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…KSR1 is an essential scaffold protein of the Ras/Raf/MAPK cascade that facilitates the activation of ERK (3). Studies have shown that the expression of KSR1 is upregulated in many types of cancer and is required for cell proliferation, apoptosis and cell-cycle reinitiation (4)(5)(6). Moreover, KSR1 was confirmed to contribute to tumorigenesis through the MAPK cascade in a mouse model (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Cav-1 has been proposed to have the ability to coordinate rapid membrane-initiate signaling pathways. Accumulating evidence suggests that Cav-1 interacts with Ras and facilitates the activation of Ras/Raf/ERK pathway (13,20), which plays a pivotal role in cell proliferation and resistance to apoptosis (18,19). Knockdown of Cav-1 expression could restrict the activation of Ras/Raf/ERK signaling pathway (16,25).…”
mentioning
confidence: 98%
“…KSR1 is then free to move to the plasma membrane with MEK in tow [5,13,14] (Figure 3(c)). The localization of KSR1 to the plasma membrane is dependent upon its interaction with Caveolin-1 and is required for KSR1-mediated ERK activation and Ras-driven transformation [18]. Once KSR1 localizes to the plasma membrane, MEK is phosphorylated by activated Raf [5,13,14,44,63].…”
Section: Ksr Proteins Are Molecular Scaffolds Of the Raf/mek/erk Kmentioning
confidence: 99%